A mutant ASXL1-BAP1-EHMT complex contributes to heterochromatin dysfunction in clonal hematopoiesis and chronic monomyelocytic leukemia - Zhen Dong; Hugo Sepulveda; Leo J. Arteaga-Vazquez; Chad Blouin; Jenna Fernandez; Moritz Binder; Wen-Chien Chou; Hwei-Fang Tien; Mrinal M. Patnaik; Geoffrey J. Faulkner; Samuel A. Myers; Anjana Rao (Proceedings of the National Academy of Sciences, 2025)
ASXL transcriptional regulator 1 (ASXL1) is one of the three most frequently mutated genes in age-related clonal hematopoiesis (CH), alongside DNA methyltransferase 3 alpha (DNMT3A) and Tet methylcytosine dioxygenase 2 ( TET2) . CH can progress to myeloid malignancies including chronic monomyelocytic leukemia (CMML) and is also strongly associated with inflammatory cardiovascular disease and all-cause mortality in humans. DNMT3A and TET2 regulate DNA methylation and demethylation pathways, respectively, and loss-of-function mutations in these genes reduce DNA methylation in heterochromatin, allowing derepression of silenced elements in heterochromatin. In contrast, the mechanisms that connect mutant ASXL1 and CH are not yet fully understood. CH/CMML-associated ASXL1 mutations encode C-terminally truncated proteins that enhance the deubiquitinase activity of the ASXL-BAP1 “PR-DUB” deubiquitinase complex, which removes monoubiquitin from H2AK119Ub. Here, we show that ASXL1 mutant proteins interact with the euchromatic histone lysine methyltransferases 1 and 2 (EHMT1–EHMT2) complex, which generates H3K9me1 and me2, the latter a repressive modification in constitutive heterochromatin. Compared to cells from age-matched wild-type mice, we found that expanded myeloid cells from old (≥18-mo-old) Asxl1tm/+ mice, a heterozygous knock-in mouse model of CH, display genome-wide decreases of H3K9me2, H3K9me3, and H2AK119Ub as well as an associated increase in expression of transposable elements (TEs) and satellite repeats. Increased TE expression was also observed in monocytes from ASXL1 -mutant CMML patients compared to monocytes from healthy controls. Our data suggest that mutant ASXL1 proteins compromise the integrity of both constitutive and facultative heterochromatin in an age-dependent manner by reducing the levels of H3K9me2/3 and H2AK119Ub. This increase in TE expression correlated with increased expression of nearby genes, including many interferon-inducible (inflammation-associated) genes (ISGs).